2021
DOI: 10.1155/2021/5613525
|View full text |Cite
|
Sign up to set email alerts
|

The Spatial Spillover Effect of Environmental Regulation and Technological Innovation on Industrial Carbon Productivity in China: A Two-Dimensional Structural Heterogeneity Analysis

Abstract: Environmental regulation and technological innovation are two crucial factors for improving industrial carbon productivity. However, prior research ignored the spatial spillover effects of these factors, and heterogeneity caused by industrialization level and resource dependence did not acquire attention either. Thus, we use the STIRPAT model and spatial panel Durbin model to study the spatial spillover effects of two independent variables. Then, a two-dimensional structural heterogeneity analysis is conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…According to the above-mentioned numerical table of coupling degrees, combined with the classification criteria of coupling degrees in the literature on the study of coupling relationships [35,36], as shown in Table 8, this study will use Mobile Information Systems the resources based on business clusters and regional innovation linkages as the basis for its conclusions. e four levels of horizontal linkage, antagonistic linkage, run-on linkage, and high-level linkage are used to measure the linkage change process of assistance based on production groups and regional innovation networks [23].…”
Section: Time Evolution Of the Coupling Between Resource-basedmentioning
confidence: 99%
“…According to the above-mentioned numerical table of coupling degrees, combined with the classification criteria of coupling degrees in the literature on the study of coupling relationships [35,36], as shown in Table 8, this study will use Mobile Information Systems the resources based on business clusters and regional innovation linkages as the basis for its conclusions. e four levels of horizontal linkage, antagonistic linkage, run-on linkage, and high-level linkage are used to measure the linkage change process of assistance based on production groups and regional innovation networks [23].…”
Section: Time Evolution Of the Coupling Between Resource-basedmentioning
confidence: 99%
“…Sun et al (2020) used the DEA method to categorize the main influencing factors of total factor carbon productivity and CO 2 emissions as technical progress, scale efficiency and management efficiency, and found that technical progress is the largest driving factor, followed by scale efficiency and management efficiency. Ren et al (2021) used the STIRPAT model and the spatial panel Durbin model to investigate the spatial spillover effects of environmental regulation and technical innovation on industrial carbon productivity in China, and found that technical innovation was beneficial to industrial carbon productivity, but there was no significant regional spillover of technical innovation. Zhang et al (2014) decomposed the influencing factors of carbon productivity into technical progress and the substitution effect between capital and labor factors and energy factor, and through further empirical research proved that technical progress has a positive promoting effect on carbon productivity, while the substitution effect between labor factor and energy factor will not be conducive to the improvement of carbon productivity.…”
Section: Factors Of Influencing Carbon Productivitymentioning
confidence: 99%
“…e implementation of cleaner production standards makes textile enterprises have technological innovation to avoid the cost of pollution control, technological progress to improve the production efficiency of enterprises, and then increase export technical complexity of enterprise. On the one hand, the implementation of cleaner production standards will promote a more rational allocation of resources and technological innovation through the cost effect [20], which will improve the productivity of enterprises [21,22]. On the other hand, in the face of environmental regulations on cleaner production, smaller or low-productivity textile enterprises cannot afford the high environmental costs and choose to exit the industry, while environmental regulations also impose sunk costs on enterprises that want to enter the textile industry, thus discouraging some enterprises from entering.…”
Section: Theoretical Mechanismsmentioning
confidence: 99%